2012
DOI: 10.5601/jelem.2012.17.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Content of minerals in grain of spring wheat cv. Koksa depending on cultivation conditions

Abstract: A study has been undertaken to determine the effect of different cultivation conditions for spring wheat cv. Koksa on the total ash, P, K, Mg, Ca, Fe, Zn, Mn, and Cu in wheat grain. The study was conducted at Uhursk Experimental Farm (51 o 18'12½N, 23 o 36'50½E) of the University of Life Sciences in Lublin, in 2008-2010. The experimental factors were: 1) systems of soil tillage: ploughing and ploughless, 2) doses of nitrogen: 90 and 150 kg ha-1 , and 3) preceding crop: pea and soy. The objective was to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Iron is considered the key metal in energy transformations needed for syntheses and other life processes of cells (Kabata-Pendias 2011). Iron content in wheat grain varies depending on the cultivar and ranges from 21.9 to 40.3 mg Fe•kg -1 (Pieczyñska et al 2011, WoŸniak andMakarski 2012). The iron quantity determined in wheat grains cv.…”
Section: Contents Of Macro-and Microelements In Grains Of Spring Wheatmentioning
confidence: 99%
“…Iron is considered the key metal in energy transformations needed for syntheses and other life processes of cells (Kabata-Pendias 2011). Iron content in wheat grain varies depending on the cultivar and ranges from 21.9 to 40.3 mg Fe•kg -1 (Pieczyñska et al 2011, WoŸniak andMakarski 2012). The iron quantity determined in wheat grains cv.…”
Section: Contents Of Macro-and Microelements In Grains Of Spring Wheatmentioning
confidence: 99%
“…Zhang et al (2012a) showed that adequate N supply can improve uptake of iron (Fe), Zinc (Zn), Manganese (Mn) and Cu in wheat grains. Standard N rate of 90 kg ha −1 increased potassium (K), Fe, Zn and Cu and 150 kg N ha -1 improved Mn uptake in grain of spring wheat (Wozniak and Makarski, 2012). McBeath et al (2011) pointed out that Phosphorus (P) should be applied in early wheat growth to provide essential P and improve grain yields.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hassan et al (2012), legumes improved P uptake of the following cereal crops. Wheat grain had higher concentrations of Calcium (Ca), Fe and Zn in cropping system after pea (Pisum sativum L.) and improved K and Mn content after soybeans (Wozniak and Makarski, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xie et al (2011) noted that applications of Nitrogen (N), Phosphorus (P) and Potassium (K) fertilizers affected soil properties, where N increased corn shoot Cu concentration and P decreased availability of Copper (Cu) and Lead (Pb). Wozniak and Makarski (2012) reported that 90 kg N ha −1 improved uptake of K, Iron (Fe), Zinc (Zn) and Cu, while high rates at 150 kg N ha −1 increased concentrations of grain Manganese (Mn) in wheat (Triticum aestivum L.).…”
Section: Introductionmentioning
confidence: 99%